Asia-Pacific consensus on the management of gastro-oesophageal reflux disease: an update focusing on refractory reflux disease and Barrett's oesophagus. Issue 9 (3rd June 2016) - Fock, Kwong Ming; Talley, Nicholas; Goh, Khean Lee; Sugano, Kentaro; Katelaris, Peter; Holtmann, Gerald; Pandolfino, John E; Sharma, Prateek; Ang, Tiing Leong; Hongo, Michio; Wu, Justin; Chen, Minhu; et al.
Abstract : Objective: Since the publication of the Asia-Pacific consensus on gastro-oesophageal reflux disease in 2008, there has been further scientific advancement in this field. This updated consensus focuses on proton pump inhibitor-refractory reflux disease and Barrett's oesophagus. Methods: A steering committee identified three areas to address: (1) burden of disease and diagnosis of reflux disease; (2) proton pump inhibitor-refractory reflux disease; (3) Barrett's oesophagus. Three working groups formulated draft statements with supporting evidence. Discussions were done via email before a final face-to-face discussion. We used a Delphi consensus process, with a 70% agreement threshold, using Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria to categorise the quality of evidence and strength of recommendations. Results: A total of 32 statements were proposed and 31 were accepted by consensus. A rise in the prevalence rates of gastro-oesophageal reflux disease in Asia was noted, with the majority being non-erosive reflux disease. Overweight and obesity contributed to the rise. Proton pump inhibitor-refractory reflux disease was recognised to be common. A distinction was made between refractory symptoms and refractory reflux disease, with clarification of the roles of endoscopy and functional testing summarised in two algorithms. The definition of Barrett's oesophagus was revised such that a minimum length of 1 cm was required and the presence of intestinal metaplasia no longer necessary. We recommended the use of standardised endoscopic reporting and advocated endoscopic therapy for confirmed dysplasia and early cancer. Conclusions: These guidelines standardise the management of patients with refractory gastro-oesophageal reflux disease and Barrett's oesophagus in the Asia-Pacific region.